Nivel de conocimiento y actitudes de adolescentes sobre prevención de infecciones de transmisión sexual en la institución educativa Nº 60188 Simón Bolívar Iquitos 2024 - Arévalo Ramírez, Ruth Karen (2025)
Sexually transmitted infections represent a priority challenge for global health, particularly among young people who initiate sexual activity at an early age. This research study examined the level of information and attitudes adopted by students at Simón Bolívar Educational Institute No. 60188 (Iquitos, 2024) regarding strategies to prevent the spread of these diseases. The study used a descriptive and correlational quantitative design, with a non-experimental, cross-sectional approach. The population analyzed included 173 adolescents selected through simple random sampling. Two tools were used for data collection: a standardized questionnaire to assess the level of knowledge and a Likert scale to measure attitudes toward prevention. The results revealed that: 54.9% of participants had insufficient knowledge about STI prevention. However, 91.3% expressed a favorable disposition toward preventive practices. Statistical analysis using the Chi-square test (χ²=6.689; p=0.010) demonstrated a significant relationship (p<0.05) between these two variables. The data confirm that more than half of adolescents lack adequate information on sexual protection, despite showing a receptive attitude toward prevention. This scenario underscores the urgency of implementing comprehensive educational programs that strengthen knowledge about sexual health. From a nursing perspective, we propose developing training interventions that transform existing positive attitudes into effective protective behaviors, thus reducing this population's vulnerability to STIs.